(untitled) - Kennedy, Mary Lynch; Kennedy, William J (Upper Saddle River, NJ, 2008)
Includes indexes.
Keywords: Academic writing -- Problems, exercises, etc.; English language -- Rhetoric; Văn bản khoa học -- Vấn đề, bài tập; Ngôn ngữ Anh -- Hùng biện